Penerapan Strategi Pemasaran Digital Pada Usaha Jamu Si Nok Dengan Menggunakan Metode Sostac - Andryas, Prasetyo; Pujianto, Totok; Putri, Selly Harnesa (Department of Agricultural Social Economics, Faculty of Agriculture, Brawijaya University, 2023)
The development of the digital era has occurred in society, running very rapidly. The occurrence of the Covid-19 pandemic has become an accelerator for people to carry out daily activities through various digital platforms, including social media. MSMEs can take advantage of the current momentum to market their products digitally so that they can be seen and purchased by the wider community. The problem with Usaha Jamu Si Nok is that it has not taken advantage of this momentum to maximize product marketing in the digital realm. This study aims to design and implement a digital marketing strategy using the SOSTAC (Situation Analysis, Objective, Strategy, Tactics, Action, Control) method. The results of the implementation of this marketing strategy are an increase in reach to 21,493 users (a rise of 10,493 users), an increase in engagement to 135 engagements (a rise of 85 engagements), and an increase in product sales of 225 products (a rise of 100 products).